Misidentification of hexagonal phase as barium carbonate during chemical synthesis of barium titanate nanopowders. (2020) - Selvaraj, M.; Venkatesan, R.; Mayandi, J.; Venkatachalapathy, V.
Abstract: Barium titanate (BaTiO3 ) nanopowders were synthesized by combining two facile route namely so-gel and hydrothermal process. The samples synthesized at 100 and 200 °C are found to exhibit cubic crystalline structure and mixed tetragonal and orthorhombic phases, respectively, as analyzed from XRD studies. In addition, characteristic peaks of unknown phase often identified as barium carbonate (BaCO3 ) was also observed. Post-annealing treatment suggests stabilization of hexagonal BaTiO3, confirmed by XRD and Raman studies.